Filial Arcade & Other Poems - Groves, Adam Staley (punctum books, 2013)
Filial Arcade & Other Poems is a book of poetry; a fusion of images and memories of a family, trees, piety, love, the sea, dying, animal life, video tapes, forests. The book is prefaced with images by Marco Mazzi.